Analysis of the Relationship between Culture of Initiative and Culture of Accuracy with Performance of Implementing Nurses at Regional General Hospital dr. Djasamen Saragih, Pematang Siantar City - Febri Aini Nasution; Zulfendri Zulfendri; Deli Theo (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze the relationship between culture of initiative and culture of accuracy with performance of implementing nurses at Regional General Hospital dr. Djasamen Saragih, Pematang Siantar City. The type of research used is descriptive research with a quantitative approach. This research was conducted from March to July 2022 at Regional General Hospital dr. Djasamen Saragih, Pematang Siantar City. The population in this study are nurses who are in the Inpatient Agencies of Regional General Hospital dr. Djasamen Saragih, Pematang Siantar City is 116 people. The method of analysis in this study uses pearson correlation test. The results show that there is a significant relationship between culture of initiative and culture of accuracy with performance of implementing nurses at Regional General Hospital dr. Djasamen Saragih, Pematang Siantar City.